Efektivitas Teknik Air Abrasion pada Preparasi Gigi terhadap Kekuatan Ikatan Resin Komposit (Laporan Penelitian) - Cinantya Putri Parahita; Ade Prijanti Dwisaptarini (Jurnal Kedokteran Gigi Terpadu, 2021)
ABSTRACTBackground:Minimal intervention dentistry promote the philosophy of prevention, remineralization, and minimal invasive in the practice of dentistry. One of the technique employed by this concept is air abrasion. Aim: to discover the effectiveness of air abrasion technique on the dental caries prepation towards the bond strength of composite resin with the method of scoping review. Method: This research utilize the PRISMA diagram, based on PubMed, PMC and Elsevier database with the keywords of: ((("air abrasion" OR "air abraded") AND (composite OR "composite resin")) AND "bond strength"). Result: Based on the criteria, 14 articles were found and divided into 5 categories Conclusion: the mean and SD of air abrasion technique with self-etch bonding type against microtensile bond strength test is 20.1 ± 5.3 - 71.7 ± 8.3 MPa; with the total-etch bonding type is 25.2 ± 7.2 - 55.08 ± 3.74 MPa, with total-etch bonding type against tensile bond strength test is 15.83 ± 1.51 - 20.80 ± 3.95 MPa; with self-etch bonding type against shear bond strength test is 6.7 - 25.32 ± 4.91 MPa; and with total etch is 13.88 ± 5.50 - 30.25 ± 7.00 MPa.